2011
DOI: 10.5586/asbp.2009.013
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds and properties of antioxidants in grapevine roots (Vitis vinifera L.) under drought stress followed by recovery

Abstract: Grapevine seedlings Vitis vinifera were grown in a greenhouse under optimum conditions (soil moisture ca 70%) and under drought stress (soil moisture ca 35%). In addition, some of the plants subjected to drought underwent subsequent regeneration under optimum conditions. Drought stress caused accumulation of total phenolic compounds in grapevine roots, which may indicate that these compounds play an important role in the adaptation of roots to growth under stress conditions. Phenolic acids found in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 22 publications
5
58
0
Order By: Relevance
“…The asterisks designate significant differences for dependent samples at p \ 0.01 (double asterisks), at p \ 0.01 (triple asterisks) Similar results were obtained in earlier research on seedlings of V. vinifera exposed to chilling stress. The total content of phenolics, tannins and phenolic acids in stress sample was lower than in control sample (Weidner et al 2009b). Furthermore, Amarowicz et al (2010) observed the same trend in leaves of V. vinifera subjected to lowtemperature stress.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The asterisks designate significant differences for dependent samples at p \ 0.01 (double asterisks), at p \ 0.01 (triple asterisks) Similar results were obtained in earlier research on seedlings of V. vinifera exposed to chilling stress. The total content of phenolics, tannins and phenolic acids in stress sample was lower than in control sample (Weidner et al 2009b). Furthermore, Amarowicz et al (2010) observed the same trend in leaves of V. vinifera subjected to lowtemperature stress.…”
Section: Discussionmentioning
confidence: 60%
“…Other experiments have demonstrated that chilling stress did not have any major effect on the total content of phenolic compounds in pea roots, but it significantly decreased the content of flavone (Rudikowskaya et al 2008). Many authors demonstrated that the production of phenols in plant tissues rises under abiotic stress conditions (Dixon and Paiva 1995;Janas et al 2002;Wróbel et al 2005;Weidner et al 2009a). Such large discrepancies in experimental results can be attributed to differences in abiotic stresses, e.g.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations